ASPEK HUKUM MENGENAI BISNIS START-UP GUNA MENDUKUNG DUNIA USAHA - Hudi Karno Sabowo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2019)
The development of human civilization, among others supported by the occurrence of the Cognitive and Science revolution. Humans have a new ability to pass on information in greater quantity about the world around them, including social relations. Limited liability company and human rights. As a result, collaboration can be established between people who do not know each other in very large numbers. Rapid social innovation. One of the interesting advances in technological innovation is the advent of internet technology. The internet changes the way people do business, socialize, share information and even change behavior and life between individuals / groups. With internet technology, it is possible to communicate without limitation of distance and time. Business start-ups emerged around 1998-2000, facing the beginning of the global economic crisis. Initially, this business was only a business for services and products that many people needed. However, since the dot-com era skyrocketed, business start-ups have become increasingly popular. No wonder the start-up business tends to be known as a business that smells of technology, sites, and the internet. Some tips for start-up businesses, what aspects need to be considered from the beginning to the start of the business. Among them are forming a CV or PT, protecting the company's brand, raising funds / capital, Special Licenses Related to Electronic Transactions and paying attention and reporting annual taxes. But more specifically, there are also a number of obstacles that must be regulated and watched out for by startups, namely the technology used, the HR that runs always innovative and can read the market well, manage the business / object being run, leadership and business management, and the necessity pay Taxation. In addition, business people or businesses should pay attention to the legal aspects of Law Number 40 of 2007 and the Republic of Indonesia Presidential Regulation of 2014 concerning Limited Liability Companies (PT). Also the Civil Code, especially Law Number 11 Year 2008 and amendment Number 19 of 2016 concerning Information and Electronic Transactions. Also the Consumer Protection Act. So, it would not hurt to try to start a business by utilizing social media technology that is owned (FB, WA, Line, etc.). However, for start-up businesses, they should pay attention to aspects such as products and brands to be marketed, and good business management and to learn and pay attention to the rules of electronic use and its legal aspects.